2019
DOI: 10.3389/fimmu.2019.01441
|View full text |Cite
|
Sign up to set email alerts
|

Claudin Family Participates in the Pathogenesis of Inflammatory Bowel Diseases and Colitis-Associated Colorectal Cancer

Abstract: Claudins are a multigene transmembrane protein family comprising at least 27 members. In gastrointestinal tract, claudins are mainly located in the intestinal epithelia; many types of claudins form a network of strands in tight junction plaques within the intercellular space of neighboring epithelial cells and build paracellular selective channels, while others act as signaling proteins and mediates cell behaviors. Claudin dysfunction may contribute to epithelial permeation disorder and multiple intestinal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 135 publications
5
69
0
1
Order By: Relevance
“…Surgery is the current treatment for solid tumor include rectal cancer. Several studies have reported that the negative effects of postoperative inflammation on prognosis in patients with colorectal cancer [23]. We have also demonstrated that post-operative LMR was closely related to the rectal cancer prognosis by multivariate regression analysis.…”
Section: Discussionsupporting
confidence: 58%
“…Surgery is the current treatment for solid tumor include rectal cancer. Several studies have reported that the negative effects of postoperative inflammation on prognosis in patients with colorectal cancer [23]. We have also demonstrated that post-operative LMR was closely related to the rectal cancer prognosis by multivariate regression analysis.…”
Section: Discussionsupporting
confidence: 58%
“…Tight junctions are pivotal in regulating intestinal permeability and maintaining intestinal barrier integrity. Emerging evidences from experimental intestinal inflammation models have supported the idea that a strong connection exists between tight junction protein impairment and intestinal inflammation [11,13].…”
Section: Introductionmentioning
confidence: 98%
“…The claudin family of proteins constitutes the tight junctions between adjacent IECs to regulate passage of ions, molecules, and barrier permeability. Shifts in the expression of tight junction proteins can result in barrier dysfunction and invasion of pathogenic bacteria across the intestinal epithelium, which are associated with the pathogenesis of IBD [28][29][30]. While previous studies have demonstrated that the STAT3 activators IL-6 and IL-22 can regulate the expression of claudin 2 to regulate intestinal permeability in vitro [31][32][33], whether this effect is observed in vivo is yet to be investigated.…”
Section: Reduction In Stat3 Activity Compromises Expression Of Antimimentioning
confidence: 99%